Analysis of Halal Assurance System Implementation and Maslahah on Processed Products in Gus Dur Cemetery - Salma Utiya Hikmah; Muhamad Ali Hisyam; Zainuddin Zainuddin (UIN Siber Syekh Nurjati Cirebon, 2024)
The obligation for Muslims to consume halal food is mandated in Surah Al-Baqarah verse 168. To ensure halal products, the Indonesian government enacted Law Number 33 of 2014 concerning the Halal Product Assurance System (SJPH). In the Gus Dur Cemetery Area, a popular pilgrimage site, the availability of halal-certified processed products is limited, raising questions about compliance with SJPH principles and their alignment with maslahah al-ammah (public benefit). This qualitative study uses an empirical approach to evaluate SJPH practices and their alignment with maslahah al-ammah. Data were collected through interviews, observations, and documentation, supported by secondary sources. Analysis followed Miles and Huberman's interactive model. The findings reveal that most processed product traders in the Gus Dur Cemetery Area have not implemented SJPH. Only two out of 53 outlets, Segere Dawet and Fruit Thai, have adopted halal certification, with others misusing halal logos without proper certification. Consequently, the maslahah al-ammah of halal food consumption is not achieved due to the incomplete implementation of halal assurance. While halal food consumption is essential for maslahah, incomplete SJPH implementation impedes its realization. Limited trader awareness and inadequate regulatory enforcement are significant challenges. The halal assurance system in the Gus Dur Cemetery Area remains insufficient, falling short of achieving maslahah al-ammah due to systemic and compliance issues.Keywords: Halal Assurance System, Maslahah, Gus Dur Cemetery, Processed Products